Influence of biocontrol agents on population density of Aspergillus flavus and kernel infection in groundnut - and K. SUBRAMANYAM, R.P. THAKUR*, V.P. RAO (Indian Phytopathology, 2003)
Aflatoxin contamination of groundnut, caused by Aspergillus ffavus (Af) group of fungi, is a major problem in the rainfed agriculture in the semi-arid tropics. Biological control could be one of the components of integrated management to reduce pre-harvest kernel infection in the field. Six Trichoderma and three Pseudomonas strains that were identified as highly antagonistic to Af 11-4 (a highly toxigenic strain) in vitro, were evaluated in field to determine their biocontrol potential. The antagonists were applied as seed dressing and soil application at flowering in Af-sick plots. All the antagonists significantly reduced seed infection in all three field experiments. Two T. viride (Tv 17 and Tv 23), one T. harzianum (Th 23), and one Pseudomonas (Pf 2) isolates provided greater protection to seed infection by Af 11-4 than others. The reduced seed contamination occurred due to significant reduction in Af population in the rhizosphere of groundnut.